Scalp as a donor site in children: Is it really the best option? - van Niekerk, Gertruida (Department of Surgery, 2020)
Introduction Humans have several different types of hair, classified into eight different groups, of which types VII and VIII predominate in South Africa. The scalp with its abundance of hair is often used as a preferential donor site for small burns. Major reasons cited are that the donor site is hidden from view (covered by hair), rapidly epithelializes with minimal scarring and provides a relatively large surface area. The author postulates that the type of hair will have an influence on the healing of scalp donor sites, complications and aesthetic outcome. Contrary to international consensus, the Red Cross War Memorial Children’s Hospital (RCWMCH) experience indicated that the use of the scalp as donor area is not ideal due to the frequent complications seen amongst paediatric patients e.g. visible scars, recurrent folliculitis, patchy alopecia, hypertrophic scarring and areas of de- and hyperpigmentation. Objective This study reviewed the complications encountered with the use of the scalp as primary donor area in children of mostly black African origin (type VI-VIII hair). Methodology A retrospective folder review of patients admitted to RCWMCH between 2003 and 2015 with major burns (>30% total body surface area) was conducted. A total of 179 patient folders were reviewed. Only children (n=25) with unburned scalp donor areas were included in this study. Both short- long-term complications were identified. The patient age range was six months - 12 years, while the mean patient follow-up period was 580 days and mean burn TBSA was 44.92% (range 4 – 85%). Results Patient demographics: black African 60% descent (hair types VI-VIII), 32% mixed race (hair types III-V) and 4% Caucasian (hair types II-III). In the group of black African children 60% had short-term and 46.7% long-term complications, whereas in the mixed race children 37.5% had short-term and 25% long-term complications. No complications were encountered in the Caucasian group. Eleven (48%) of patients in total had short-term complications (88.9% folliculitis, 22.2% delayed healing) and seven (28%) had long-term complications (57,1% non-healing wounds, 42.8% recurrent folliculitis, 57.1% alopecia, 42.9% depigmented scars, 28.6% visible scars, 28.6% hypertrophic scars). The first procurement in 11 children resulted in a 91% complication rate (54.5% short-term and 36.4% long-term). Ten children had two procurements resulting in an 80% complication rate (40% short-term and 40% long-term complications). In four children with three scalp procurements an acute 25% complication rate, with no subsequent long-term complications, was encountered. Discussion Hair type has an influence on outcome and donor sites should be carefully selected. Hair types VI-VIII has a higher propensity for complications and these usually follow the first procurement procedure. Complications did not increase with multiple procurements. Significant complications with long-term sequelae are not uncommon when the scalp is used as donor site and these complications are difficult to treat. Although the sample size is small, it does reflect a significant complication rate. Conclusion Contrary to international consensus, the use of the scalp as donor site in South African children with hair types VI-VIII with large burns should not be the preferential site and should only be used as a last resort.